Digest: Propagule pressure might not matter in the establishment of invasive prokaryotes. (10th December 2019) - Peniston, James H.
Abstract: Lavigne et al. developed models to investigate the adaptive colonization of sink environments by asexual organisms. Their results have clear relevance to the spread of infectious disease, but they may also provide insights into prokaryotic invasions into natural communities. Their results show that propagule pressure might not be a good predictor of invasion success in prokaryotes, suggesting that more work is needed to understand how microbial invasions differ from those of plants and animals.